Analisis Integrasi Nilai Spiritual QS. Al -‘Alaq Ayat 1-5 Dalam Pembelajaran IPA di Era Society 5.0 - Fauzan, Ahmad (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the integration of spiritual values derived from QS Al-‘Alaq verses 1–5 into science education in the era of Society 5.0. A descriptive qualitative method was employed, with data collected through questionnaires, interviews, and documentation, and analyzed using the Miles and Huberman model. A total of 48 students were selected purposively as research subjects. The findings revealed that 80.7% of students understood QS Al-‘Alaq 1–5 as a spiritual foundation for science learning, and 87.0% were aware of their role as khalifah (stewards of the Earth). A high level of enthusiasm (86.5%) was shown in connecting Qur’anic verses with scientific concepts, although understanding of Society 5.0 remained limited (74.0%). The developed teaching module fostered transformative learning by integrating science, technology, and religious values. Technical Triangulation results indicated a strong understanding of QS Al-‘Alaq (80.7%) and a high level of motivation to study science (87.0%). Enthusiasm for integrating the Qur’an with science was high (86.5%), supported by a project-based learning approach. Understanding of Society 5.0 needs to be further enhanced. Overall, students demonstrated highly positive attitudes toward sustainable and religious-based learning (88.5%), with 85.4% expressing readiness to apply Islamic-based science. In conclusion, the integration of values from QS Al-‘Alaq into science education strengthens students’ awareness and positions science as a pathway to sustainable education.